APPLYING ITEM RESPONSE THEORY TO IDENTIFY RESPONDENTS’ TENDENCY TO CHOOSE MIDDLE OPTION ON PSYCHOLOGY SCALE - Wahyu Widhiarso (Proyeksi: Jurnal Psikologi, 2012)
The question of how large the proportion of respondents who tend to choose the middle option onpersonality scale was difficult to answer since it depends on two factors: respondents themselves anditems. Due to recent development of psychometric theory, this question can be answered by combiningsuch factors into one model. One of the representative models which can facilitate this combination isMixed Rasch Modeling (MRM). This study applied this model to identify respondents’ tendency tochoose the middle option on the psychological scale. The research data obtained from measurements ofthe five personality factors in 200 students. Analysis result which was performed separately on eachpersonality factors suggest that proportion of respondents who chose the middle option is quite smalland only occurs on two personality factors (27 percent in extroversion and 11 percent on opennessfactor). Additional finding showed that respondents who have a tendency to choose the middle optiononly perform in certain items than all items.